2003
DOI: 10.1177/0193841x02239019
|View full text |Cite
|
Sign up to set email alerts
|

Methods To Reduce The Impact Of Intraclass Correlation In Group-Randomized Trials

Abstract: This study reports intraclass correlation (ICC) for dependent variables used in group-randomized trials (GRTs). The authors also document the effect of two methods suggested to reduce the impact of ICC in GRTs; these two methods are modeling time and regression adjustment for covariates. They coded and analyzed 1,188 ICC estimates from 17 published, in press, and unpublished articles representing 21 studies. Findings confirm that both methods can improve the efficiency of analyses shown to be valid across cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
206
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(214 citation statements)
references
References 42 publications
8
206
0
Order By: Relevance
“…Conventional single-level analytical approach is inadequate to obtain valid statistical results when the ICC is large. Murray and Blitstein (2003) have reported that the school-level ICCs for the majority of health behaviors is less than 0.05 indicating low degree of dependence in observations. Therefore, ICCs were calculated for variables in the model and all were found to be less than 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional single-level analytical approach is inadequate to obtain valid statistical results when the ICC is large. Murray and Blitstein (2003) have reported that the school-level ICCs for the majority of health behaviors is less than 0.05 indicating low degree of dependence in observations. Therefore, ICCs were calculated for variables in the model and all were found to be less than 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…Although group randomized designs require larger scale interventions, recent innovations to address problems with intraclass correlations mitigate such problems to a certain degree. 77 Another quantitative approach that is especially well suited for AIAN communities is the multiple baseline design. This adaptation of a research design for singleparticipant and small-N studies involves gathering data across multiple study sites; the intervention is implemented at each site at time-lagged intervals.…”
Section: Culturally Specific Assessment and Intervention Methodsmentioning
confidence: 99%
“…To assess potential confounding, we examined group differences between sociodemographic variables and basic needs at baseline. Because we did not find any meaningful confounding, and per Murray and Blistein's 35 suggested method, we chose covariates (race, marital status, and maternal employment) that reduced the intraclass correlation effect for our regression models. Additionally, for all outcome measures collected after the index visit, we adjusted the models for duration of follow-up time.…”
Section: Sample Size and Statistical Analysismentioning
confidence: 99%